2000
DOI: 10.3109/07435800009048613
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Tumorigenesis Targeted by the Corticotropin-Regulated Promoter of the Aldo-Keto Reductase AKR1B7 Gene in Transgenic Mice

Abstract: Studies of ACTH functions in adrenal steroidogenesis have been facilitated by the availability of immortalized mouse adrenocortical Y1 cells. In order to obtain alternative cell lines with a more differentiated zona fasciculata (ZF) phenotype we used targeted tumorigenesis strategy. We have generated transgenic mice expressing the SV40 T antigen under the control of the ACTH-dependent promoter for the AKR1B7/MVDP gene (aldo-keto reductase 1B7/mouse vas deferens protein), which encodes an enzyme responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…1A) were able to confer ZF-specific and ACTH-regulated expression to reporter genes in transgenic mice, recapitulating the essential features of the endogenous gene expression in the adrenal gland (42,43). These cis-acting sequences driving the SV40 large T antigen were shown to induce the formation of cortical tumors in two founder transgenic mice (44). The cells from two of these independent tumors, ATC1 and ATC7-L, were propagated for up to 40 passages without crisis, indicating immortalization.…”
Section: Establishment Of Acth-responsive Adrenocortical Cell Lines Fmentioning
confidence: 95%
See 2 more Smart Citations
“…1A) were able to confer ZF-specific and ACTH-regulated expression to reporter genes in transgenic mice, recapitulating the essential features of the endogenous gene expression in the adrenal gland (42,43). These cis-acting sequences driving the SV40 large T antigen were shown to induce the formation of cortical tumors in two founder transgenic mice (44). The cells from two of these independent tumors, ATC1 and ATC7-L, were propagated for up to 40 passages without crisis, indicating immortalization.…”
Section: Establishment Of Acth-responsive Adrenocortical Cell Lines Fmentioning
confidence: 95%
“…These cell lines were designated ATC1 and ATC7-L for ATC of founder transgenic mice 1 and 7-Left adrenal, respectively (44). ATC cells were cultured on polylysincoated 10-cm tissue culture dishes in a 1:1 mixture of DMEM and Ham's F-12 medium (DMEM-F12) at 37 C in a 5% CO 2 -95% air atmosphere.…”
Section: Establishment and Culture Of Adrenocortical Tumor Cell (Atc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Promotors that have been used to target the adrenal cortex include 5'-flanking sequences from the human CYP11A gene (Compagnone et al, 1997), the aldose reductase-like (akr1b7) gene (Sahut-Barnola et al, 2000), and the inhibin-α promotor (Kananen et al, 1996). In particular, the inhibin-α promotor driven transgenic animal (inhα/Tag) has been phenotypically characterized in great detail and a large body of literature demonstrates the gonadectomy-dependent induction of adrenocortical tumorigenesis (Kananen et al, 1997;Rilianawati et al, 2000;Rilianawati et al, 1998).…”
Section: Genetically Modified Mouse Models With Actsmentioning
confidence: 99%
“…These include isocaproic aldehyde, derived from the cholesterol side chain discarded by the action of CYP11A, and free radicals that may be generated by 'leaky' P450s. It has been suggested that enzymes such as the aldose reductase-like AKR1B7 and MnSOD may be present in steroidogenic tissues for this reason (Sahut-Barnola et al 2000, Suwa et al 2000.…”
Section: Introductionmentioning
confidence: 99%